2010
DOI: 10.1208/s12249-010-9394-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rosuvastatin on the Serum Cortisol, Serum Lipid, and Serum Mevalonic Acid Levels in the Healthy Indian Male Population

Abstract: Abstract.In this open-label, balanced, randomized, placebo-controlled, parallel study, healthy male volunteers were randomly divided into two groups. Each group received either a single oral dose of rosuvastatin 20 mg or placebo. Estimations were done at predose on day 1 of dosing (baseline) and 24 h postdose after days 7 and 14. Serum cortisol and serum lipid levels were estimated using enzyme-linked immunosorbent assay kits and serum mevalonic acid (MVA) levels were measured using validated liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Until now, however, the use of enzymatic spectrophotometric methodology has been precluded by the extremely low levels of MVA in human plasma and serum. The normal range of MVA concentration has been reported to be 1.0-11.2 ng/ml (6.7-75.6 nmol/l) in plasma ( 9 ) and 12.28 ± 2.54 ng/ml (82.9 ± 17.1 nmol/l) in serum ( 11 ). In the present study, we describe a simple, precise, and ultrasensitive enzymatic method for measuring MVA in serum .…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Until now, however, the use of enzymatic spectrophotometric methodology has been precluded by the extremely low levels of MVA in human plasma and serum. The normal range of MVA concentration has been reported to be 1.0-11.2 ng/ml (6.7-75.6 nmol/l) in plasma ( 9 ) and 12.28 ± 2.54 ng/ml (82.9 ± 17.1 nmol/l) in serum ( 11 ). In the present study, we describe a simple, precise, and ultrasensitive enzymatic method for measuring MVA in serum .…”
mentioning
confidence: 76%
“…These include a radioenzyme assay ( 2 ), enzyme immunoassay ( 3 ), GC-MS assay ( 4-7 ), and LC-MS/MS assay (8)(9)(10)(11)(12)(13). Until now, however, the use of enzymatic spectrophotometric methodology has been precluded by the extremely low levels of MVA in human plasma and serum.…”
mentioning
confidence: 99%
“…35,36 The impact of statins on adrenal function has been studied in multiple populations with a wide variety of statins. 23,[25][26][27][28][29]31,32,[37][38][39][40][41][42][43][44][45] None of these studies showed clinically relevant impairment of adrenal function, secondary to statin therapy. Patients with heterozygous or homozygous familial hypercholesterolemia could also theoretically be at increased risk of adrenal dysfunction because of their reduced capacity to use LDL receptor-mediated cholesterol uptake.…”
Section: 22mentioning
confidence: 97%
“…49 Two studies of adrenal function in patients treated with rosuvastatin did not find any impairment in adrenal function despite lowering LDL-C to a mean of 1.5 mmol/L (59 mg/dL) and 1.6 mmol/L (61 mg/dL), respectively. 27,31 In another study of patients selected on the basis of LDL-C <1.8 mmol/L (70 mg/dL), with a mean LDL-C of 1.5 mmol/L (58 mg/dL), adrenal function was also normal. 50 In our study, we observed no evidence of hypoadrenalism (decreased cortisol, increased ACTH, or a decreased cortisol:ACTH ratio) in evolocumab-treated patients, even in those achieving very low LDL-C.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation